Answer:
[tex]v_{f} = \frac{mv_{1} +3mv_{2} }{4m}= \frac{v_{1} +3v_{2}}{4}\\[/tex]
[tex]change in K = (\frac{1}{2} mv_{1}^{2} - \frac{1}{2}.3mv_{2} ^{2} ) - \frac{1}{2}(4m)v_{f}^{2}[/tex]
Explanation:
Using the principle of conservation of momentum
momentum before the collision = momentum after the collision
[tex]mv_{1} + 3mv_{2} = (m+3m)v_{f}\\mv_{1} + 3mv_{2} =4mv_{f}\\v_{f} = \frac{mv_{1} +3mv_{2} }{4m}= \frac{v_{1} +3v_{2}}{4}\\[/tex]
Change in kinetic energy = sum of kinetic energies after the collision - sum of kinetic energies before the collision
[tex]change in K = (\frac{1}{2} mv_{1}^{2} - \frac{1}{2}.3mv_{2} ^{2} ) - \frac{1}{2}(4m)v_{f}^{2}[/tex]
The simplification for kinetic energy can be made by substitution the answer for the first part into the second part